2023
DOI: 10.1038/s41467-023-36602-0
|View full text |Cite
|
Sign up to set email alerts
|

Acidic graphene organocatalyst for the superior transformation of wastes into high-added-value chemicals

Abstract: Our dependence on finite fossil fuels and the insecure energy supply chains have stimulated intensive research for sustainable technologies. Upcycling glycerol, produced from biomass fermentation and as a biodiesel formation byproduct, can substantially contribute in circular carbon economy. Here, we report glycerol’s solvent-free and room-temperature conversion to high-added-value chemicals via a reusable graphene catalyst (G-ASA), functionalized with a natural amino acid (taurine). Theoretical studies unveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Meanwhile, FeCl 3 /γ‐Al 2 O 3 catalyst was recovered from the reaction system by separation, washing and calcination at 300 °C for 2 h to remove adsorbed H 2 O and organic matter. The glycerol conversion, Solketal selectivity and Yield of Solketal were gotten based on the following equations (1‐3) [31a,39] : Conversionofglycerol%=GlycerolconvertednormalmnormalonormallInitialglycerolnormalmnormalonormall×100% $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm C}{\rm o}{\rm n}{\rm v}{\rm e}{\rm r}{\rm s}{\rm i}{\rm o}{\rm n}{\rm \ }{\rm o}{\rm f}{\rm \ }{\rm g}{\rm l}{\rm y}{\rm c}{\rm e}{\rm r}{\rm o}{\rm l}{\rm \ }\left({\rm \char37 }\right)=\hfill\cr {{{\rm G}{\rm l}{\rm y}{\rm c}{\rm e}{\rm r}{\rm o}{\rm l}{\rm \ }{\rm c}{\rm o}{\rm n}{\rm v}{\rm e}{\rm r}{\rm t}{\rm e}{\rm d}{\rm \ }\left({\rm m}{\rm o}{\rm l}\right){\rm \ }}\over{{\rm I}{\rm n}{\rm i}{\rm t}{\rm i}{\rm a}{\rm l}{\rm \ }{\rm g}{\rm l}{\rm y}{\rm c}{\rm e}{\rm r}{\rm o}{\rm l}{\rm \ }\left({\rm m}{\rm o}{\rm l}\right)}}\times 100\hskip0.17em{\rm \char37 }\hfill\cr}}$ Selectivity…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, FeCl 3 /γ‐Al 2 O 3 catalyst was recovered from the reaction system by separation, washing and calcination at 300 °C for 2 h to remove adsorbed H 2 O and organic matter. The glycerol conversion, Solketal selectivity and Yield of Solketal were gotten based on the following equations (1‐3) [31a,39] : Conversionofglycerol%=GlycerolconvertednormalmnormalonormallInitialglycerolnormalmnormalonormall×100% $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm C}{\rm o}{\rm n}{\rm v}{\rm e}{\rm r}{\rm s}{\rm i}{\rm o}{\rm n}{\rm \ }{\rm o}{\rm f}{\rm \ }{\rm g}{\rm l}{\rm y}{\rm c}{\rm e}{\rm r}{\rm o}{\rm l}{\rm \ }\left({\rm \char37 }\right)=\hfill\cr {{{\rm G}{\rm l}{\rm y}{\rm c}{\rm e}{\rm r}{\rm o}{\rm l}{\rm \ }{\rm c}{\rm o}{\rm n}{\rm v}{\rm e}{\rm r}{\rm t}{\rm e}{\rm d}{\rm \ }\left({\rm m}{\rm o}{\rm l}\right){\rm \ }}\over{{\rm I}{\rm n}{\rm i}{\rm t}{\rm i}{\rm a}{\rm l}{\rm \ }{\rm g}{\rm l}{\rm y}{\rm c}{\rm e}{\rm r}{\rm o}{\rm l}{\rm \ }\left({\rm m}{\rm o}{\rm l}\right)}}\times 100\hskip0.17em{\rm \char37 }\hfill\cr}}$ Selectivity…”
Section: Methodsmentioning
confidence: 99%
“…Owing to their distinct chemical and physical characteristics (with a breaking strength of 42 N m −1 and Young's modulus of ≈1.0 terapascals), high electron mobility (>200 000 cm 2 (V s) −1 at low temperatures), [130] strong thermal and chemical stabilities, conductivity (≈3000 W m −1 K −1 ), and optoelectronic properties, applications of graphene and its derivatives have been extended to a much broader areas, such as energy storage, adsorption, water splitting, photocatalysis, biosensors, and biomedical. [68,[131][132][133][134][135][136] One plausible approach to harness these characteristics for applications would be to integrate graphene sheets in composite material using different design methods, such as solution mixing/impregnation, in situ polymerization, coating, and melt grinding, [135,137] as shown in Figure 13. Li et al [138] prepared graphene foam-based nanocomposite using paraffin wax.…”
Section: Graphene and Its Derivativesmentioning
confidence: 99%
“…30 Recently, Zbořil et al reported the transformation of wastes into high-added-value chemicals using GO as an organocatalyst. 31 With our interest towards the development of environmentally friendly synthetic methodologies, herein we revealed a highly green and efficient synthesis of 3,3′,3″-trisindoles using GO as a heterogeneous catalyst in DMSO/water medium. This is the first report on a carbene-transfer reaction using GO as a highly green and reusable catalyst (Scheme 1f ).…”
Section: Introductionmentioning
confidence: 98%
“…30 Recently, Zbořil et al reported the transformation of wastes into high-added-value chemicals using GO as an organocatalyst. 31…”
Section: Introductionmentioning
confidence: 99%